Advances in Cryptology
DOI: 10.1007/3-540-39568-7_36
|View full text |Cite
|
Sign up to set email alerts
|

Poker Protocols

Abstract: The situation is quite serious. After four years of research, there has been no satisfactory way for a group of card sharks to play poker over the phone. Until now. In this paper, we present a new method for playing 'mental poker,' discuss its significance, and mention some of the further questions it r a b s. Ante up. The rules for mental poker are just like regular poker, except that players communicate over the phone, and there are no physical cards. The hard part of mental poker is dealing the cards. Hands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Cryptographers have shown that a small amount of information is leaked by these poker protocols if the RSA public-key algorithm is used [453,573]. Specifically, if the binary representation of the card is a quadratic residue (see Section 11.3), then the encryption of the card is also a quadratic residue.…”
Section: Attacks Against Poker Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptographers have shown that a small amount of information is leaked by these poker protocols if the RSA public-key algorithm is used [453,573]. Specifically, if the binary representation of the card is a quadratic residue (see Section 11.3), then the encryption of the card is also a quadratic residue.…”
Section: Attacks Against Poker Protocolsmentioning
confidence: 99%
“…Other research on poker protocols can be found in [573,1634,389]. A complicated protocol that allows players to not reveal their hands can be found in [390].…”
Section: Attacks Against Poker Protocolsmentioning
confidence: 99%
“…Mental poker is one of the most popular games of online gambling and the fairness of the involved players is challenging from the view point of data security. Mental poker was firstly proposed by Shamir et al [13] in 1979 and many attempts have been made to achieve protocols that would allow people to play mental poker [8,14,9,1,15,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Mental poker protocols with a TTP [10,8,1] are normally simple and efficient. However, the assumption of a fully trusted TTP is not tolerable in online gambling.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not easy to design a fast enough protocol to satisfy practical needs. Despite many protocols have been proposed ( [2,3,7,9,8,16,15,18,20,21,23,25,27,28,29]), online poker rooms are still based on client-server architectures. Therefore, online players are assumed to trust the server.…”
mentioning
confidence: 99%